2006
DOI: 10.1080/10350330600664821
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Citizenship through the Lens of Consumerism: Frames in the American Medicare Reform Debates of 2003–2004

Abstract: Abstract:Access to health care is an issue that challenges the imagined boundary between being a 'consumer' and being a 'citizen'. This is especially true in the United States where marketbased solutions to providing health care have historically been favored over care organized through government. In the recent debate over how to organize prescription drug coverage for seniors in the United States, stakeholders quoted in the press were more likely to position health care as a consumer issue rather than as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Patients' Bill of Rights debate. West's (2006) study of Medicare reform news coverage, as previously noted, tallied specific word counts related to: citizen, consumer, and patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' Bill of Rights debate. West's (2006) study of Medicare reform news coverage, as previously noted, tallied specific word counts related to: citizen, consumer, and patient.…”
Section: Methodsmentioning
confidence: 99%
“…The examination of word choice in health care public policy debates is well established. West (2006) looked at the Medicare prescription drug coverage debate in [2003][2004], specifically the terminology used by both news media and institutional sources such as the American Medical Association, President George W. Bush, and the American Association of Retired People. She concluded that the word choice reflected more of a consumer than citizen model, especially among the institutional sources.…”
Section: Introductionmentioning
confidence: 99%
“…A strand of this critical work addresses the commodification of health care, and the transformation of health care users into consumers (Lupton, 1994;West, 2006;Zoller, 2008). A key insight is that while consumerism connotes choice and empowerment, it is also a tool of discipline (de Souza, 2011;Lupton, 1995;Rose, 2007).…”
mentioning
confidence: 99%
“…7 In wealthy nations at least, the question is now less one of separating ill and healthy populations than the government of life itself, the intense capitalization of our efforts to maximize our corporeal existence, present and future, especially as it unfolds at the level of the molecule. 8 If biopolitics shapes definitions and practices of citizenship, gender, race, sexuality, pleasure, and danger, how does this modeling capacity jump scale from laboratories and hospitals and forge broad social and political effects?…”
mentioning
confidence: 99%